Values of Islamic Religious Education in QS. Al-Duha Verse 9-11 - Zubairi, Zubairi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The work in education must be directed to the preparation of the complete human being, as its material should be comprehensive of all human aspects, and this is because the human being is a complete and indivisible unit, so his education must be a complete and indivisible unit as well. And if the scholars divide education into sections, this is nothing but to specify its material and facilitate work in it. The method used in this research is a literature review related to the problem under study. The results of the study show that the educational process that all educators and parents must take care of is to raise students and children with wisdom and good exhortation and earnest for them the following is better, with a soft and good saying, and this is related to the verse of the Qur’an in Surat Adh-Duha, verse 9-11.